2021
DOI: 10.3390/ijms22094667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lacosamide Treatment on Epileptogenesis, Neuronal Damage and Behavioral Comorbidities in a Rat Model of Temporal Lobe Epilepsy

Abstract: Clinically, temporal lobe epilepsy (TLE) is the most prevalent type of partial epilepsy and often accompanied by various comorbidities. The present study aimed to evaluate the effects of chronic treatment with the antiepileptic drug (AED) lacosamide (LCM) on spontaneous motor seizures (SMS), behavioral comorbidities, oxidative stress, neuroinflammation, and neuronal damage in a model of TLE. Vehicle/LCM treatment (30 mg/kg, p.o.) was administered 3 h after the pilocarpine-induced status epilepticus (SE) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…These results are similar to those of Mishra et al (2021a) and suggest anti-amnesic-and anxiolytic-like properties. These findings confirm the antiepileptogenic potential of the plant extract since working memory impairment, anxiety disorders, and epileptogenesis share similar bidirectional and cause-toeffect links (Shishmanova-Doseva et al, 2021;Suleymanova, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…These results are similar to those of Mishra et al (2021a) and suggest anti-amnesic-and anxiolytic-like properties. These findings confirm the antiepileptogenic potential of the plant extract since working memory impairment, anxiety disorders, and epileptogenesis share similar bidirectional and cause-toeffect links (Shishmanova-Doseva et al, 2021;Suleymanova, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…As previously described, SE was induced by an intraperitoneal injection of Pilo (320 mg/kg), 30 minutes after administration of scopolamine methyl nitrate 1 mg/kg i.p [ 61 , 62 ]. Seizure severity was evaluated based on the Racine scale [ 63 ].…”
Section: Materials and Methodsvmentioning
confidence: 99%
“…The anxiety index (AI) was calculated as follows: AI = 1 − [(open arms time/total time) + (number of entries in open arms/total number of entries)/2]. The alleys of the maze were cleaned with ethanol solution (60% volume) after the removal of each rat [ 63 , 65 ].…”
Section: Materials and Methodsvmentioning
confidence: 99%
“…These data show that the inhibition of the TLR4/NF-κB inflammatory pathway can improve the emotional and behavioral disorders of epileptic rats. Studies have shown that a large number of hippocampal neurons die after epileptic seizure ( 25 , 50 52 ), which may be related to microglias promoting epileptic-induced neurogenesis ( 53 , 54 ). In the TUNEL experiment, neuronal apoptosis was greater in rats in the EP group, and the expression in rats in the two treatment groups, the EP+BAY group and EP+TAK group, was better than that of rats in the EP group.…”
Section: Discussionmentioning
confidence: 99%